Ekspansi Pemasaran dan Pemanfaatan Platform Digital untuk Mendukung Pelestarian Budaya dan Peningkatan Ekonomi Kampung Adat Banceuy - Lani Nurlani; Agin Sugiwa; Sari Azhariyah; Rendi Perdiansah; Muhammad Taufik Hidayat; Riski Fitriani; Andi Hermawan; Tegar Kusuma; Tasya Novita Ananda (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Banceuy Traditional Village is a traditional village in Subang Regency with rich cultural heritage and significant natural tourism potential. However, the community still faces various challenges in developing this potential, particularly in the relatively simple packaging of local products and the limited use of digital technology for marketing. This community service activity aims to increase community capacity through product packaging training and the implementation of an integrated digital platform, the Warisanbanceuy.com website, which can be used for product management, news, cultural events, homestays, and more. The results of the activity demonstrate that the community is able to create attractive and marketable product packaging and utilize the digital platform to expand marketing reach and promote culture. This technology implementation has resulted in increased community digital literacy and opened up new economic opportunities based on local potential.